A two dimensional analytical modeling of surface potential in triple metal gate (TMG) fully-depleted Recessed-Source/Drain (Re-S/D) SOI MOSFET. (April 2016) - Priya, Anjali; Mishra, Ram Awadh
Abstract: In this paper, analytical modeling of surface potential is proposed for new Triple Metal Gate (TMG) fully depleted Recessed-Source/Dain Silicon On Insulator (SOI) Metal Oxide Semiconductor Field Effect Transistor (MOSFET). The metal with the highest work function is arranged near the source region and the lowest one near the drain. Since Recessed-Source/Drain SOI MOSFET has higher drain current as compared to conventional SOI MOSFET due to large source and drain region. The surface potential model developed by 2D Poisson's equation is verified by comparison to the simulation result of 2-dimensional ATLAS simulator. The model is compared with DMG and SMG devices and analysed for different device parameters. The ratio of metal gate length is varied to optimize the result. Highlights: Triple metal gate Recessed Source-Drain MOSFET. Reduced DIBL and short channel effect. Surface potential for oxide thickness. Surface potential for channel thickness. Surface potential for recessed source drain thickness.